A proline-derived transannular N-cap for nucleation of short α-helical peptides. Issue 59 (30th June 2016) - Tian, Yuan; Wang, Dongyuan; Li, Jingxu; Shi, Chuan; Zhao, Hui; Niu, Xiaogang; Li, Zigang
Abstract : We report herein a simple and practical proline-derived transannular N-cap as a helix nucleating template in diverse bio-related peptide sequences via macrolactamization on resin. Abstract : We report herein a proline-derived transannular N-cap as a helix nucleating template in diverse bio-related peptide sequences via macrolactamization on resin. This approach takes advantage of synergistic stabilization effects of both N-capping properties of proline and substitution of a main chain hydrogen bond with a covalent bond.